The Role of Financial Literacy and Financial Behavior on Student Investment Decisions - Wijayanti, Rahmah Putri; Azizah, Elmy Nur; Kurniawan, Herwin (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to see how financial literacy and financial behaviour can affect investment decision making for university students. Methods: This study is a quantitative study. Sample determination using purposive sampling method with a total of approximately 200 people. Data collection is using a questionnaire with a Likert scale (1-5). The results of obtaining data from the questionnaire will be analysed using descriptive data analysis techniques and processed using SEM PLS software.  Results: the results of the above research state that financial literacy and financial behaviour have a significant effect on investment decisions in college students. The Investment Decision Variable can be explained by Financial Literacy and Financial Behaviour by 51%.